Transnational Smuggling and Illegal Migration in Africa: Causes and Effects - Nwala , Paul; Gesiere, Lolia (Kashere Journal of Politics and International Relations, 2023)
Transnational smuggling and illegal migration have become pressing issues in contemporary Africa, with profound social, economic, and political implications. This research study aims to investigate the root causes and far-reaching effects of these phenomena on the African continent. Through a comprehensive analysis of historical, socio-economic, and geopolitical factors, this research sheds light on the motivations behind illegal migration and the networks facilitating it, including human trafficking, drug smuggling, and arms trafficking but the center of this study is focused more on human illegal migration and goods smuggling which has somewhat contributed to the underdevelopment of Africa. It also highlights the consequences, effects or impacts these activities have on Africans, ranging from increased security concerns to strained resources in host countries, as well as the exploitation and vulnerability of migrants. The study adopted a qualitative form of research method gotten from primarily secondary sources of online and journal materials with some bits of statistics and rate numbers of areas it was necessary. By providing an in-depth examination of the causes and effects of transnational smuggling and illegal migration in Africa, this research aims to contribute to a deeper understanding of these complex issues and inform policies and interventions that address them through the remedy provided here in.